Dielectric Resonator Matching Model For Stability Performances Of Microwave Amplifier - Yob, Rashidah Che (2019)
The stability factor and matching techniques on microwave amplifier have been an important consideration in order to maintain the required performances, such as high power for the high power amplifier and low noise for low noise amplifier. Simultaneously, the issues of stability need more attention to avoid the presence of the oscillations and make it performs as the amplifier without failed. Typically, the stability factor and matching techniques of the amplifier are frequency dependent. Thus, a variable frequency mechanism is required in order to ascertain the amplifier to be operated resides within the stable region. The dielectric resonator is incorporated as the variable frequency mechanism purposely to tackle this issue. The characteristics of the dielectric resonator are evaluated on their physical parameter and material with different topologies of the parallel microstrip line. The obtained best configuration of the dielectric resonator is represented by the 155 ° curves configuration with 19 mm parallel microstrip line spacing for same waveguide port position. This configuration of the dielectric resonator is incorporated as the dielectric resonator matching model for stability performances of microwave amplifier. This investigation is evaluated for conditional stable and unconditional stable transistors at 5 GHz. In addition, the new dielectric permittivity is developed through their scattering parameters responses that referred to the previous transistor used investigation, especially dielectric resonator oscillator applications. The obtained of new dielectric permittivity that refers to the stable operating frequency of previous transistor used investigation is adopted into the best configuration of the proposed dielectric resonator as the homogenous dielectric resonator. As results, the dielectric resonator matching model can be used for both conditional stable and unconditional stable transistors in maintaining their stability performances. The stability performances are greater than 1 which shown the microwave amplifier is operated in a stable region and successfully minimize the oscillation occurrences. Furthermore, the proposed dielectric resonator matching model has the potential to act as a variable frequency mechanism by the adopted different dielectric permittivity. Concurrently, the dielectric resonator matching model is easier to do adjustment after fabrication compared to the conventional matching method of microwave amplifier.